Illustrating war-time: Cartoons and the British and Dominion soldier experience during the Great War, 1914–1918. (July 2019) - Chapman, Jane; Wilson, Ross
This article assesses how time was depicted within illustrated narratives published in trench newspapers and regimental journals by British and Dominion soldiers as a means of adapting to and enduring the experience of the First World War. Through an extensive archival study of these sources, soldiers' 'comic strips' have been used to demonstrate that time is illustrated as a personal and social experience that enables individuals to comprehend their role within the army. Previous assessments of the experience of time on the battlefields have been dominated by the perception that mechanized warfare induced a fractured and disorientating sense of time. This has traditionally been heralded by scholars as indicating the arrival of a new 'modern era'. However, research findings demonstrate the way in which soldiers illustrated time, the passing of time, the use of order, experience and progress are evident. Far from reflecting the alienating effect of modern warfare, soldiers illustrate 'war-time' as a means by which they inculcate themselves into a military culture and continue their role in the war.